MEGIBUNG DALAM PEMERTAHANAN TRADISI ADAT DAN BUDAYA DI DESA ADAT KEMONING KECAMATAN KLUNGKUNG KABUPATEN KLUNGKUNG DILIHAT DARI DIMENSI NILAI MORAL PANCASILA - I NYOMAN BAYU PERMANA (Jurnal Pendidikan Kewarganegaraan Undiksha, 2013)
ABSTRACTThis study aimed to describe (1) the philosophical foundations megibung tradition, (2) the procession megibung tradition, and (3) indigenous traditions megibung terms of moral values of Pancasila. What this research is in thetraditional village Kemoning, Klungkung district, Klungkung regency. This study used purposive sampling technique so that the subject of research is the traditional village heads, community leaders, and youth. Data was collected through interviews, literature, observation, and recording of documents. The data were analyzed by descriptive qualitative data were analyzed by using words. These results indicate (1) the foundation of the tradition megibung philosophy is to instill a pattern of togetherness, mutual cooperation, unity, justice, democracy, humanity and divinity in life, (2) be gradual procession megibung the preparation, processing, presentation, megibung, and stage finishes megibung, and (3) in the tradition of megibung when viewed from the moral values of Pancasila. All the moral values of Pancasila was conducted in the tradition megibung. It can be concluded that megibung tradition has a very close correlation with the moral values of Pancasila and also very pronounced nuances.Keywords: Megibung and Indigenous Traditions